Simplify each of the following. Assume a, x, and y are not zero. 1) 103 over 102 2) –x2y over (x2)2 y2 1.) 103 over 102
= 101 {when dividing, subtract the exponents} = 10 2.) –x2 over (x2)2 y2 = x2 over x4 y2 {when you have a power to a power, multiply exponents} = 1 over x2 y2 {cancel x2 with x4}  Algebra House
1 Comment
Some Guy
12/8/2012 08:30:25 pm
In #2, I believe the x^2 becomes 1 because the x^2 becomes x^0 when you cancel it, which basically ends up as 1
Reply
Your comment will be posted after it is approved.
Leave a Reply. 
Latest Videos
Examples
All
